Vitamin D status is not associated with inflammatory cytokine levels during experimental human endotoxaemia. (3rd January 2013) - Kox, M.; van den, M. J. W.; van der, J. G.; Wielders, J. P. M.; van der, A. J.; Pickkers, P.
Summary Vitamin D has been shown to modulate innate immune responses in vitro and ex vivo; however, human in‐vivo data are lacking. At high latitudes, seasonal vitamin D deficiency is common due to alternating ultraviolet (UV)‐B radiation exposure. In the present study, we investigated whether levels of 25 hydroxyvitamin D3 [25(OH)D3] and its active metabolite 1, 25 dihydroxyvitamin D3 [1, 25(OH)2D3] are subject to seasonal variation and whether plasma levels of these vitamin D metabolites correlate with the in‐vivo cytokine response during experimental human endotoxaemia [administration of lipopolysaccharide (LPS) in healthy volunteers]. Plasma levels of 25(OH)D3 and 1, 25(OH)2D3 were determined in samples obtained just prior to administration of an intravenous bolus of 2 ng/kg LPS (derived from Escherichia coli O:113) in 112 healthy male volunteers. In the same subjects, plasma levels of the inflammatory cytokines tumour necrosis factor (TNF)‐α, interleukin (IL)‐6 and IL‐10 were analysed serially after endotoxin administration. Plasma levels of 1, 25(OH)2D3, but not 25(OH)D3, were subject to significant seasonal variation, with lower levels in autumn and winter. 25(OH)D3 and 1, 25(OH)2D3 levels did not correlate with plasma cytokine responses. Furthermore, 25(OH)D3 deficient subjects (< 50 nmol/l) displayed an identical cytokine response compared with sufficient subjects. In conclusion, plasma levels of vitamin D are not correlated with the LPS‐induced TNF, IL‐6 and IL‐10 cytokine response in humans in vivo. These findings question the direct role of vitamin D in modulation of the innate immune response.